STRATEGI HUMOR PADA ACARA STAND UP COMEDY - Utami, Indah Ita (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
Stand Up Comedy is a type of single joke because comedians perform monologue on a stage alone and rely on their gestures. This research is to answer these problems: what are the pragmatic strategy, linguistic strategy, humor function, and the community's response to humor strategies of children comedians in the Stand Up Comedy program? This study uses descriptive qualitative method. This study uses three stages, namely the stage of the data collection, the data analysis stage, and the stage of presenting the results of data analysis. The methods used in the data collection stage are observation and interview. The data analysis phase uses the pragmatic equivalent method. The stage of presenting the results of data analysis uses informal methods. The pragmatic of the strategies that are dominantly used are presuppositions, violation of maxim, and implicature. The dominant strategies of linguistic that are found are nonsense, ridicule, irony, and misunderstanding. The dominant function of humor that is found tends to give an understanding to the community to find solutions to a problem through ways that are conveyed pleasantly. However, the community judges that some of the words uttered tend to give a bad example because they seem impolite and patronizing.